2014
DOI: 10.1080/00036846.2014.962223
|View full text |Cite
|
Sign up to set email alerts
|

The effect of conservatism on cost of capital: MENA evidence

Abstract: The purpose of this article is to investigate the economic consequences of accounting conservatism in the Middle Eastern and North African (MENA) region. In particular, motivated by the lack of such studies in the context of emerging countries, we empirically examine the effect of conditional conservatism on firms' cost of equity capital. Using a sample of firms pertaining to 13 MENA countries during the period 2004-2007, we conduct three sets of tests. First, we assess the existence of conservatism in our sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 45 publications
(113 reference statements)
5
18
1
Order By: Relevance
“…They further found that conservatism regularly declines the improvement of the firm's information environment. It is also supported by the results of (Khalifa & Ben Othman, 2015;Zare et al,. 2013;Lara et al, 2011;Gietzmann & Trombetta, 2003).…”
Section: Results Of Main Research Hypotheses Testsupporting
confidence: 81%
See 1 more Smart Citation
“…They further found that conservatism regularly declines the improvement of the firm's information environment. It is also supported by the results of (Khalifa & Ben Othman, 2015;Zare et al,. 2013;Lara et al, 2011;Gietzmann & Trombetta, 2003).…”
Section: Results Of Main Research Hypotheses Testsupporting
confidence: 81%
“…The results of the full sample model revealed that accounting conservatism and voluntary disclosure have significant negative impacts on the firms' cost of capital. (Khalifa & Ben Othman, 2015) examined the economic results of accounting conservatism in emerging economies, particularly in the region of the Middle East and North Africa by using three models include well-known Basu's (1997) model to assess the presence of conservatism, the effect of conservatively reporting bad news and good news on the cost of equity capital, and disaggregated their measurements of conditional conservatism into conservatism with respect to bad news and conservatism with respect to good news. Their results revealed that both have the same negative impact on the cost of equity capital, which implies that conservatism provides the same amount of information irrespective of the type of news.…”
Section: Introductionmentioning
confidence: 99%
“…However, evidence of such effects, as reported in these studies, is mixed and inconclusive. For example, Francis et al (2004) report no significant association, Chan et al (2009) and Biddle et al (2012) show a positive association, however, Artiach and Clarkson (2014) Garcia et al (2011), Khalifa and Ben Othman (2015) and Li (2014) find a negative effect of accounting conservatism on the cost of equity capital. The apparent inconsistency of the findings may be ascribed to the regression approach employed to test such association (Rush et al (2014)).…”
Section: Introductionmentioning
confidence: 97%
“…Foreign investors will therefore be concerned withthe rate of return (Firm's COEC) that receives in exchange for their investments. Moreover, firms in MENA countries are recognized as applying accounting conservatism practices (Khalifa and Ben Othman, (2015) and Khalifa et al, (2016)). Therefore, MENA emerging countries is an interesting context for examining the association between accounting conservatism and the cost of equity.…”
Section: Introductionmentioning
confidence: 99%
“…The findings of the study demonstrate that cost of capital decreases as the degree of conservatism in the firm increases. Another concurrent study conducted by Khalifa and Othman (2015) utilizes the firm-specific measure of conditional conservatism developed by Khan and Watts (2009) The relationship has also been evaluated with an emphasis on debt capital by the early work of Ahmed et al (2002). They discuss that conservative accounting policies tighten dividend policy, which results in a reduction in the amount of return required by bondholders as the risk of excessive dividend payments is mitigated.…”
Section: Literature Reviewmentioning
confidence: 99%